Implementing the Repeated Reading Method to Improve Reading Fluency among Fourth-Grade Students in an Inclusive Elementary School - Husnul Nisa; Fery Muhamad Firdaus (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aimed to describe the implementation of the Repeated Reading method in an inclusive Year 4 classroom, examine improvements in reading fluency, and identify changes in the motivation and self-confidence of a student with special educational needs. Classroom Action Research was conducted in two cycles, each comprising three 70-minute sessions. Participants were 26 students, including one student with special educational needs. Quantitative data were collected using curriculum-based oral reading fluency measures to assess words correct per minute (WCPM) and accuracy, alongside a multidimensional scale for prosody. Qualitative data were obtained through classroom observations and reflective records. Implementation fidelity increased from 85.7% in Cycle I to 92.9% in Cycle II. Mean WCPM rose from 79.42 to 99.42, while classical mastery increased from 26.9% to 76.9%. Mean prosody scores improved from 59.94% to 85.26%, with mastery reaching 88.5%, and mean reading accuracy increased from 73.12% to 77.43%. The student with special educational needs also demonstrated greater enthusiasm, confidence, and reading motivation. These findings indicate that Repeated Reading effectively improves reading fluency and supports positive affective development in an authentic inclusive classroom.